Two-colour pump-probe experiments with a twin-pulse-seed extreme ultraviolet free-electron laser - Allaria, Enrico E M; Bencivenga, F.; Borghes, R.; Capotondi, Flavio; Castronovo, D.; Charalambous, P.; Cinquegrana, P.; Danailov, M. B.; De Ninno, G.; Demidovich, Alexander; Di Mitri, Simone; Diviacco, B.; et al. (Nature Communications, 2013)
Exploring the dynamics of matter driven to extreme non-equilibrium states by an intense ultrashort X-ray pulse is becoming reality, thanks to the advent of free-electron laser technology that allows development of different schemes for probing the response at variable time delay with a second pulse. Here we report the generation of two-colour extreme ultraviolet pulses of controlled wavelengths, intensity and timing by seeding of high-gain harmonic generation free-electron laser with multiple independent laser pulses. The potential of this new scheme is demonstrated by the time evolution of a titanium-grating diffraction pattern, tuning the two coherent pulses to the titanium M-resonance and varying their intensities. This reveals that an intense pulse induces abrupt pattern changes on a time scale shorter than hydrodynamic expansion and ablation. This result exemplifies the essential capabilities of the jitter-free multiple-colour free-electron laser pulse sequences to study evolving states of matter with element sensitivity. © 2013 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2022-07-20